2011
DOI: 10.1042/bj20102096
|View full text |Cite
|
Sign up to set email alerts
|

Farnesoid X receptor protects human and murine gastric epithelial cells against inflammation-induced damage

Abstract: Bile acids from duodenogastric reflux promote inflammation and increase the risk for gastro-oesophageal cancers. FXR (farnesoid X receptor/NR1H4) is a transcription factor regulated by bile acids such as CDCA (chenodeoxycholic acid). FXR protects the liver and the intestinal tract against bile acid overload; however, a functional role for FXR in the stomach has not been described. We detected FXR expression in the normal human stomach and in GC (gastric cancer). FXR mRNA and protein were also present in the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
(8 reference statements)
3
28
0
Order By: Relevance
“…Besides the intestinal system, kidneys, liver or adrenal glands, FXR exhibits a low expression level in the stomach, heart, lung and fat tissue (9,11,12,(27)(28)(29). In the present study, we observed FXR expression at a significantly lower level in cultured human GES-1 gastric mucosa cells and assessed the functional connection between bile acid-FXR pathway and intestinal metaplasia of gastric mucosa cells.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Besides the intestinal system, kidneys, liver or adrenal glands, FXR exhibits a low expression level in the stomach, heart, lung and fat tissue (9,11,12,(27)(28)(29). In the present study, we observed FXR expression at a significantly lower level in cultured human GES-1 gastric mucosa cells and assessed the functional connection between bile acid-FXR pathway and intestinal metaplasia of gastric mucosa cells.…”
Section: Discussionmentioning
confidence: 75%
“…It was reported that activation of the FXR pathway in mice is able to resist the gastrointestinal mucosal damage of non-steroidal anti-inflammatory drugs (NSAIDs) (30). FXR functions to protect gastric epithelial cells against inflammation-mediated damage (11). Those findings suggest that proper stimulation of FXR serves as a type of protective mechanism for mucosa.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The therapeutic potential of bile acids and derivatives for treating hepatic and biliary diseases, NAFLD, and metabolic syndrome has been extensively reviewed Fiorucci and Baldelli, 2009;Zollner and Trauner, 2009;Lian et al, 2011;Pols et al, 2011a,b;Adorini et al, 2012;Hollman et al, 2012;Stojancevic et al, 2012;McMahan et al, 2013;Mudaliar et al, 2013;Stepanov et al, 2013;Duboc et al, 2014) and will be briefly summarized. Bile acid sequestrants have long been used for treating gallstone disease.…”
Section: Fatty Liver Disease Diabetes and Obesitymentioning
confidence: 99%
“…It was concluded that FXR activation in the ileum is reduced in Crohn's patients, secondary to altered enterohepatic circulation of bile acids. TGR5 and FXR agonists may have therapeutic benefit to Crohn's disease patients (Lian et al, 2011;Pols et al, 2011b;Stojancevic et al, 2012;Stepanov et al, 2013).…”
Section: B Inflammatory Gastrointestinal Diseasesmentioning
confidence: 99%